Mural sebagai Media Peningkatan Kesadaran Siswa SMA akan Pentingnya Merawat Tanaman - Muhammad Rifqi; Puri Kurniasih; Irwan Maolana Yusup (CV Buana Prisma Sejahtera, 2023)
This community service activity aims to help partners realize the visual message of environmental awareness through mural media. The message of environmental care was chosen because environmental issues are one of the main issues that concern the world today. The issue is then focused into the theme of plants. In the implementation process, this activity was carried out with collaboration between the DKV Unindra Lecturer Team and the SMAN 3 Depok Teacher Team, especially during the planning and sketching process. Furthermore, in making the mural, this activity also involved DKV Unindra students and SMAN 3 Depok students who voluntarily participated. Through this collaboration and participation, it is hoped that not only the teachers and students will gain insight into the mural, but also foster a sense of ownership of the mural.